An immunofluorescent study of the distribution of immunoglobulin-containing cells in the normal and the inflamed human gall bladder. Issue 5 (May 1972) - Green, F. H. Y.; Fox, H.
Abstract : Immunoglobulin-containing cells are present in the normal human gall bladder but they are much less numerous in this site than in the normal intestine. IgA-containing cells predominate in the mucosa but in the muscle layer IgM cells are the more numerous. In both acute and chronic inflammation of the gall bladder there is a marked increase in the number of immunoglobulin-containing cells. In all but the most severe cases of inflammation it is those cells containing IgA which show the greatest increase in numbers, but in severe cases there is a disproportionate rise in the number of IgG- and IgM-containing cells, these latter being possibly derived from the blood. IgA cannot be demonstrated in the epithelial cells of the gall bladder and positive evidence of secretion into the bile of locally produced immunoglobulin is lacking. It is suggested that the concentration of IgA normally present in bile is such that, irrespective of local production, some is derived from the serum or the intestine.